The Prevalence and Associated Risk Factors of Uncontrolled Hypertension amongst Antihypertensive Medicines Taking Patients - Asad Ullah Khan, Shaikh Fahad Falah, Syeda Anmol Saba Shah, Inam-U-Llah, Aqsa Aslam, Ambreen Anjum, Nadia Shabnam, Maira Iqbal, Sudhair Abbas Bangash, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to determine how common uncontrolled HTN is among medicated hypertensive individuals in Pakistan. Study Design: Cross-sectional study Place and Duration: This study was carried out at Hayatabad Medical Complex from Jan 2022 to April 2022 Methods: Total 165 hypertensive patients of both genders were presented. Enrolled cases were aged between 18-80 years. Baseline detailed demographics included age, sex, body mass index and socio economic status were recorded. Frequency of anti-hypertensive medications and uncontrolled hypertension among all cases were assessed. SPSS 24.0 was used to analyze all data. Result: Majority of the patients 95 (57.6%) were females and 70 (42.4%) were males. Mean age of the patients was 60.4±9.30 years and had mean BMI 30.3±17.85 kg/m2. 101 (61.2%) patients had poor socio-economic status. Frequency of married patients was 130 (78.8%) cases and 105 (63.6%) cases were non-educated. Mean duration of hypertension was 5.8±6.20 years. Most frequently used antihypertensive drug was combination therapy. Frequency of uncontrolled hypertension was found in 82 (49.7%) cases. Males, people older than 60, and smokers were more likely to experience uncontrolled hypternsion. Obesity, hyperlipidemia, diabetes, anaemia, malignancy, and reflex or gastric reflux disease were all associated with an increased risk of uncontrolled hypternsion in individuals with comorbid illnesses (P <0.05). Conclusion: According to the findings, there is an urgent requirement for more productive measures aimed at enhancing HTN control. Patients with hypertension who also smoke cigarettes, have diabetes, have a poor education level, and have a body mass index that is greater than normal should be the focus of the efforts. Keywords: Un-controlled hypertension, Comorbidities, Anti-Hypertensive Medications, Risk Factors